2013
DOI: 10.4028/www.scientific.net/amr.663.335
|View full text |Cite
|
Sign up to set email alerts
|

A Cataluminescence-Based Sensor for Detecting Benzene, Toluene and Xylene Vapors Utilizing the Catalytic Reduction on the Surface of Nanosized Al<sub>2</sub>O<sub>3</sub>/Pt

Abstract: A new gas sensor was designed based on cataluminescence (CTL) by using catalytic reduction of benzene, toluene and xylene (BTEX) on the surface of nanosized catalyst Al2O3/Pt with hydrogen as the carrier gas. The result indicated that the sensor showed strong CTL response, high selectivity and excellent durability under optimal conditions: Al2O3/Pt (1%), the temperature of 395oC, the wavelength of 425 nm and the flow rate of 270 mL/min. The detection limit (3σ) is 0.2 ppm for benzene, 0.3 ppm for toluene and x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The suitable working temperature and airflow are beneficial to the sensitivity of the sensor [22–27]. In order to explore the optimum conditions for the detection of the four alcohols, the effects of temperature and airflow on the relative CTL produced by the four alcohols on the surface of the material were investigated, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The suitable working temperature and airflow are beneficial to the sensitivity of the sensor [22–27]. In order to explore the optimum conditions for the detection of the four alcohols, the effects of temperature and airflow on the relative CTL produced by the four alcohols on the surface of the material were investigated, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have shown that temperature and air flow rate have a great influence on the intensity of CTL [22][23][24][25][26][27]. Therefore, under the condition of keeping other conditions unchanged, we investigated the CTL intensity of trichloroethylene on the surface of PEG200/ZnO nanocomposite at different temperatures and air flow rate in order to obtain better response conditions, the specific results are shown in Fig.…”
Section: Effect Of Working Temperature Air Flow Rate and Analyte Conmentioning
confidence: 99%
“…3b shows that with the increase of air flow rate, CTL signal and signal-to-noise ratio (S/N) increase at first and then decrease. The reason for this result may be that when the air flow rate reaches a certain value, the contact time between the detector and the sensor is not enough, which reduces the sensitivity of the detection system [26,27]. Using this as a reference, the suitable carrier air flow rate of the sensor can be determined to be 180 mL / min.…”
Section: Effect Of Working Temperature Air Flow Rate and Analyte Conmentioning
confidence: 99%
“…CTL refers to the phenomenon according to which when a catalytic oxidation reaction occurs at the gas-solid interface, the substance absorbs energy from the ground state and converts it into an excited state, and the excited state releases energy into the ground state, accompanied by chemiluminescence [13]. The CTL method based on nanomaterials is a new sensor detection method, which is widely studied and applied to the detection of volatile organic compounds (VOCs) in the environment [14][15][16][17][18][19]. Shi et al [20] prepared Pt/NU-901 nanocomposites for CTL sensors to detect acetone, a marker of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that Pt has good oxidation resistance and high conductivity, and platinum can provide excitation electrons in CTL sensors. Therefore, adding it to a CTL sensor will further enhance the detection signal of the sensor and speed up its response and recovery time [19,[34][35][36]. Therefore, Pt was used as decoration to prepare Pt/Ti 3 C 2 T x -CNT catalyst in this paper.…”
Section: Introductionmentioning
confidence: 99%